Theory of Event Coding (TEC) V2.0: Representing and controlling perception and action - Hommel, Bernhard (Attention, perception & psychophysics, 2019)
This article provides an update of the Theory of Event Coding (TEC), which claims that perception and action are identical processes operating on the same codes – event files consisting of integrated networks of sensorimotor feature codes. The original version of the theory emphasized its representational underpinnings, but recent theoretical developments provide the basis for a more integrated view consisting of both the codes that are shared between perception and action in the control processes operating on these codes. Four developments are discussed in more detail: The degree to which the integration and retrieval of event files depends on current goals, how metacontrol states impact the handling of event files, how feature binding relates to event learning, and how the integration of non-social events relates to the integration of social events. Case examples using various versions of the Simon task are used to explain how the new version of TEC explains interactions between perception and action in non-social and social situations.